Cerpen-cerpen Lekra (1950—1965) sebagai strategi perjuangan politik PKI - Junaidi, Ahmad Syafa'at; Wasono, Sunu; Zulyeno, Bastian (Universitas Mulawarman, 2023)
This study aims to reveal the contents and objectives contained in Lekra's short stories, which were published in Harian Rakjat in 1950–1965. The data source for this research is in the form of short stories: Paman by L.S. Retno, Gambar Pemimpin by Saibun, Kebangunan di Kota Bengawan by Namikakanda, and Loper by Putu Oka. This research is qualitative, using library research methods. The results of the study show that these short stories are loaded with political interests of the PKI as part of the PKI's struggle to influence the masses so that the PKI succeeds in the political competition in Indonesia in 1950–1965. In addition, these short stories show that there is a close relationship between literature (Lekra), politics (PKI), and the media (Harian Rakjat). From this relationship, literature and the media at that time were under political control. Lekra as a cultural institution in Indonesia became a political tool for the PKI to influence the ideology of readers and its supporters, and the Harian Rakjat was used by the PKI as a medium for spreading it. Basically, both Lekra and Harian Rakjat were tools for realising PKI politics, and both were in positions facilitated by the PKI.